Induction of Labour: Change of Method and its Effects - Kehl, Sven; Weiss, C.; Dammer, U.; Raabe, E.; Burghaus, Stefanie; Heimrich, J.; Hackl, J.; Winkler, Michael; Beckmann, Matthias; Faschingbauer, Florian (Geburtshilfe und Frauenheilkunde, 2015)
Aim: The combination of mechanical and drug procedures for the induction of labour seems to be beneficial. Accordingly, the normal procedure in clinical routine has been changed and induction of labour by means of a balloon catheter has been implemented. The aim of this study was to find out if this procedural change has resulted in a more effective induction of labour. Materials and Method: In this historical cohort study 230 inductions of labour at term in the year 2012 were compared with 291 inductions of labour in the year 2013, all at the University of Erlangen Perinatal Centre. Exclusion criteria were, among others, a multiple pregnancy, a premature rupture of membranes and a prior Caesarean section. In 2012 births were induced solely by use of the drugs dinoprostone and misoprostol, in 2013 not only with misoprostol but also mainly by use of a balloon catheter. The primary target parameter was the rate of failed labour inductions, defined as "no birth within 72 hours". Results: Altogether 521 inductions of labour were analysed. The rate of failed inductions of labour could be reduced by the changes in induction method (first-time mothers: 23 vs. 9 %, p = 0.0059; multiparous women: 10 vs. 1 %, p = 0.0204). Furthermore, the rate of primary Caesarean sections due to failed induction of labour (5.7 vs. 1.4 %, p = 0.0064), that of the observation of green amniotic fluid (first-time mothers: 23 vs. 9 %, p = 0.0059; multiparous women: 10 vs. 1 %, p = 0.0204) and of infantile infections (first-time mothers: 23 vs. 9 %, p = 0.0059; multiparous women: 10 vs. 1 %, p = 0.0204) were all reduced as well. Conclusion: The routine use of a balloon catheter for induction of labour has markedly improved the procedure. There were fewer failed labour inductions and fewer Caesarean sections due to failed induction of labour.
EVALuna2:17598